The Impact of Tourism on Senior Well-being: A Study of IMSERSO Programmes - Ruiz-Moreno, Carolina; Picón-Berjoyo, Araceli; Rodríguez-Serrano, M. Ángeles; Domínguez-CC, Marta (Journal of Tourism, Sustainability and Well-being, 2024)
The well-being of older people is currently a priority, due both to the rapid ageing of the population and the negative effects generated by the COVID 19 pandemic. Under the “Active and Healthy Ageing” approach, different sorts of activities, especially tourism, and their influence on improving the well-being of older people are analysed. The effects of tourist activities on people’s well-being are supported in many studies, however, there are few works focused on older people and, specifically, the most disadvantaged who attend social programmes. The main research question in this study is to analyse whether participation in a social tourism programme has a positive influence on the subjective well-being of older people. Likewise, age, gender, frequency and duration of trips, and their impacts on well-being are all analysed. To do so, a sample of seniors who had participated in IMSERSO trips (Spanish Institute for the Elderly and Social Services) was surveyed to quantify their levels of well-being after the trip. The results showed that they presented high levels of subjective well-being and that age, gender, and frequency of trip were factors that impacted on that perception. With regard to the trip itself, those who travelled more frequently presented higher levels of well-being, while the influence of trip duration was not significant.